What was achieved at the Dubai COP28 Climate Conference: Opinion note - Russo Andrade, Ricardo Omar (2024)
The opinion note presents the author's evaluation of the accomplishments of The COP28 climate conference in Dubai, which took place from November 30 to December 12, 2023. It is noted that a significant level of consensus was achieved during the conference. A notable majority of nations, such as the European Union (EU), the Alliance of Small Island States (AOSIS), the United Kingdom, Australia, Canada, and the United States, acknowledged the imperative of transitioning away from fossil fuels. Despite facing resistance from major oil-producing nations in the region, the conference managed to arrive at acceptable resolutions by the conclusion of the event.